Erdafitinib Antagonizes ABCB1-Mediated Multidrug Resistance in Cancer Cells - Feng, Weiguo; Zhang, Meng; Wu, Zhuo-Xun; Wang, Jing-Quan; Dong, Xing-Duo; Yang, Yuqi; Teng, Qiu-Xu; Chen, Xuan-Yu; Cui, Qingbin; Yang, Dong-Hua (Frontiers in Oncology, 2020)
ABCB1 overexpression is known to contribute to multidrug resistance (MDR) in cancers. Therefore, it is critical to find effective drugs to target ABCB1 and overcome MDR. Erdafitinib is a tyrosine kinase inhibitor (TKI) of fibroblast growth factor receptor (FGFR) that is approved by the FDA to treat urothelial carcinoma. Previous studies have demonstrated that some TKIs exhibit MDR reversal effect. In this work, we examined whether erdafitinib could reverse MDR mediated by ABCB1. The results of reversal experiments showed that erdafitinib remarkably reversed ABCB1-mediated MDR without affecting ABCG2-mediated MDR. The results of immunofluorescence and Western blot analysis demonstrated that erdafitinib did not affect the expression of ABCB1 or its cellular localization. Further study revealed that erdafitinib inhibited ABCB1 efflux function leading to increasing intracellular drug accumulation, thereby reversing MDR. Furthermore, ATPase assay indicated that erdafitinib activated the ABCB1 ATPase activity. Docking study suggested that erdafitinib interacted with ABCB1 on the drug-binding sites. In summary, this study demonstrated that erdafitinib can reverse MDR mediated by ABCB1, suggesting that combination of erdafitinib and ABCB1-substrate conventional chemotherapeutic drugs could potentially be used to overcome MDR mediated by ABCB1.